The Phenomenon of FOMO as Consumptive Behavior of Generation Z in Purchasing Traditional Food (Case Study of Lawar Macho Rena) - Ida Ayu Elistyawati; I Gusti Ayu Ratna Pramesti Dasih; Gusti Ayu Putu Darmayanti (Brilliant International Journal Of Management And Tourism, 2025)
Fear of Missing Out (FoMO), or the fear of missing out on new information or trends that emerge, is one of the phenomena that emerge as a result of the influence of social media. In terms of food, FoMO makes Generation Z want to try viral foods so as not to be considered out of date. This case study uses a qualitative method with a phenomenological approach, using observation and interviews. A qualitative method with a phenomenological approach was used to collect and interview ten Gen Z informants. The results showed that Generation Z's social media content encouraged 85% of respondents to try or follow trends on social media. However, this study found that it was not only Generation Z's social media content that created a desire to try or follow trends on social media; among them, Hedden influenced Gen Z's interest in buying traditional food by 60%, unique or ancient names influenced Gen Z's interest by 70%, and traditional food stalls that were legendary influenced Gen Z's interest by 75%. Generation Z believes that legend food is delicious because it still exists today.